Some aspects of the biology of invasive fish species from a Langat River tributary, Selangor, Malaysia - Olawale Saba, Abdulwakil; Mohd Arshad, Muhammad Shakir Zufayri; Abdul Razak, Muhammad Afifuddin; Kamal, Amirah Mustafa; Abdullah Halim, Muhammad Rasul; A Ghani, Intan Faraha; Ilham-Norhakim, Mohd Lokman; Amal, Mohammad Noor Azmai (Universiti Putra Malaysia Press, 2024)
Invasive fish species pose several threats to aquatic biodiversity and health, necessitating a good understanding of their biology and ecology. This study aims to understand the biology of invasive fish species collected from a Langat River tributary, Selangor, focusing on their growth, reproduction, and feeding habits. Fish and water samples were collected between March and August 2022. A total of 171 specimens were recorded, including 71, 55, and 45 individuals of Pterygoplichthys disjunctivus, P. pardalis, and Oreochromis sp. The b values for length-weight relationships of P. disjunctivus, P. pardalis, and Oreochromis sp. were 2.79, 2.92, and 2.89, respectively. The mean condition factor for Oreochromis sp. was significantly (p < 0.05) higher than that of the other two species. There were no significant differences between the observed and expected number of males and females for all three species. The females had higher mean gonadosomatic index values compared to males. The mean fecundity for P. disjunctivus, P. pardalis, and Oreochromis sp. were 973 ± 596, 10562 ± 830, and 1052 ± 1068, respectively. The most important stomach contents of the three species were detritus, mineral particles, and diatoms, with a higher proportion of mineral particles found in the diets of P. disjunctivus and P. pardalis. The information on growth patterns, reproductive strategies, and dietary preferences provides valuable insights for controlling their invasion of local rivers.